The association between training and organizational citizenship - Ahmad, K.Z. (2009)
This research investigates the association between five training variables (availability of training, Support for training, motivation to learn, training environment and perceived benefits of training and various aspects of organizational citizenship behaviour (OCB). A questionnaire survey was conducted on 120 employees in the banking industry in Malaysia. OCB was made up of 5 components - altruism, conscientiousness, civic virtue, sportsmanship and courtesy. OCB was measured by the 21-item questionnaire developed from Podsakoff, MacKenzie, Moorman and Fetter (1990); PodsakojJ and MacKenzie, (1994). The training questionnaire was adopted from /(amarul and Raida (2003). Support for training, motivation to learn, training environment, and benefits of training are all significantly correlated with all components of OCB with the exception Of sportsmanship.